Product Brand Awareness through Gimmick Humor Content - Nurrochman, Ferry Dwi; Adelia, Dena; Aryakhiyah, Layya; Erawati, Dedet (Syntax Literate, 2024)
A digital marketing strategy using humorous gimmicks can steal the company's attention because it attracts the audience's attention and can increase brand awareness of a Pocari Sweat product. Aiming to find out what marketing strategies can be used on social media and whether digital marketing strategies using humorous gimmicks can grow brand awareness of a product, this research uses a descriptive qualitative method using theory from Dentsu; in this theory, there is the AISAS model, namely (Attention, Interest, Search, Action, Share). The research results show that a marketing strategy using humorous gimmicks can provide added value to brand awareness because it has a strong appeal in the eyes of the audience and can entertain the audience. The clever gimmick content strategy used by Fadil Jaidi has proven to be an effective digital marketing strategy that impacts brand awareness of a product. From informants' responses and netizen comments on his Instagram account, the audience does not see endorsement advertising content because of the interest built through the humorous gimmick presented. The content created by Fadil Jaidi has also successfully increased the audience's buying interest, thus influencing the social media of brands or products that Fadil Jaidi collaborates with.